Penyuluhan Tentang Edukasi Asi Eksklusif Guna Persiapan Pemberian Asi Eksklusif di PMB Nosita Damayanti Simo - Winarsih, Winarsih; Widyaning Pertiwi, Herdini; Revika, Era (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Exclusive breastfeeding has been stated in various regulations and legislation in Indonesia. One of them is based on the decision of the Minister of Health of the Republic of Indonesia Number 450/MENKES/SK/IV/2004 concerning exclusive breastfeeding..According to Roesli, this is because breast milk is the right intake because its composition always adapts to the baby's body and the development of the systems within the body. Education is expected to be a means of obtaining information, knowledge and a means of discussing problems faced by breastfeeding mothers.How to increase mothers' knowledge and understanding regarding the importance of preparing for exclusive breastfeeding through exclusive breastfeeding education for pregnant women so as to increase coverage of exclusive breastfeeding in Simo Village, Boyolali Regency. Methods for implementing outreach activities aboutExclusive breastfeeding education to prepare for exclusive breastfeeding at PMB Nosita Damayanti SimoThis is a method of health education in the form of counseling. The target is third trimester pregnant women who are members of the pregnant women class. The result was that there were 15 counseling participants who experienced an increase in knowledge after being given education about exclusive breastfeeding from 21 participants. Advice for pregnant women in the third trimester is to give breast milk as soon as the baby is born until 6 months. Keywords: Education, exclusive breastfeeding